Moderating Effect of Religiosity on Islamic Green Banking Interest as a Supporting Factor for Sustainable Finance - Fauzani; Anisah; Yeni Oktaviani (Yayasan Darussalam Bengkulu, 2026)
Background: Sustainable finance has gained global attention, with ESG principles becoming increasingly important in the Islamic banking sector. However, public ESG literacy and bank reputation remain limited, influencing interest in Islamic green banking. This study analyzes the influence of ESG literacy and bank reputation on interest in Sharia green banking, with religiosity as a moderating variable. Method: This quantitative study employed a moderated regression analysis (MRA) using SPSS to test both direct and moderating effects. Data were collected through questionnaires distributed to 200 respondents selected via purposive sampling in Sarolangun Regency, with criteria of being at least 18 years old, aware of Islamic banks, and familiar with sustainability or green banking issues. Results: The findings indicate that ESG literacy and bank reputation have a positive and significant influence on interest in Sharia green banking, both partially and simultaneously. The t-test results show ESG literacy (t=2.283, p=0.023) and bank reputation (t=2.521, p=0.036) significantly affect interest. The F-test confirms joint significance (F=23.061, p=0.000). Religiosity was found to amplify the influence of both ESG literacy (p=0.021) and bank reputation (p=0.011) on interest. The adjusted R² value of 0.354 indicates that the independent variables explain 35.4% of the variation in interest. Conclusion: ESG literacy and bank reputation positively influence interest in Islamic green banking, with religiosity strengthening this relationship. These findings provide an empirical basis for strengthening Islamic banks' educational and reputational strategies to encourage public participation in a just and sustainable green economy.